Thermal Comfort Assessment of An Office Room Under High Air Conditioning Setting Temperatures with Fan-Assisted Ventilation - Zakaria, M. A.; Amran, M. S.; Rozmi, S. A.; Yasin, M. N.; Leng, P. C.; Hanipah, M. H. (International Journal of Integrated Engineering, 2022)
The usage of the air-conditioning system to provide comfortable indoor conditions is found necessary especially for hot-and warm countries. However, the excessive use of the air-conditioning system or without properly controlled will significantly affect the energy consumption of the building and also the environment badly. This study investigates the strategy to reduce energy for cooling in an office room by utilizing the high setting temperature of the air conditioning system with the addition of fan ventilation by field measurement. About 9 study cases have been investigated which includes the air-conditioning setting of 27°C to 28°C, with and without fan-assisted ventilation. The measured physical thermal comfort parameters are air temperature, relative humidity, wind speed, and black globe temperature. The operative temperature and Predicted Mean Vote value (PMV) have been calculated for each study case for analysis. The results revealed that the comfortable condition with neutral sensation can be achieved by air-conditioning setting of 28°C with an air speed of 1 m/s-1.2m/s. Moreover, the results showed that the room with 27°C-28°C setting temperature was under comfortable conditions before afternoon hours, while fan-assisted ventilation is required to enhance the comfortable hours through the rest working hour. By this practice, it is expected the energy consumption and cooling load of the building can be reduced.